Do Financial Analysts Perform a Monitoring Role in China? Evidence from Modified Audit Opinions. (6th September 2016) - Chen, Jiandong; Ding, Rong; Hou, Wenxuan; Johan, Sofia
Abstract : This paper examines the impact of analyst coverage on the financial reporting quality of firms as reflected by modified audit opinions (MAOs). Using a sample of Chinese listed firms between 2003 and 2009, we find that analyst coverage, which serves as an external governance mechanism, helps to enhance the financial reporting quality of Chinese listed firms. The effect is more pronounced for non‐state‐owned enterprises (i.e., private firms), in that they are more dependent on external equity capital and, therefore, under greater pressure from analysts to provide high‐quality accounting information. Furthermore, analysts play a more effective role for firms with stronger incentives to manipulate financial reports. Our findings are robust to the control of endogeneity issue.